The influence of ethnic group work culture on organizational performance: the moderating effect of organizational culture - Usman, Ahmed; Abdulkarim, Siraj (2016)
The purpose of this study is to investigate the influence of ethnic group work culture on organizational performance among three major ethnic group that from various departments and units of Kaduna state public service, secondly, to explore the moderating effect of organizational culture on the relationship between ethnic group work culture and performance.A sample of 205 directors and unit heads from the various departments and units of Kaduna state public service.A web-based survey were used to generated data and data analysis using partial least square (PLS) path modeling. The study revealed that the ethnic group work culture was found positively and significantly affect organizational performance. In same vain the moderating effect of organizational culture on the relationship between ethnic group work culture and organizational performance was full moderated.